Territorial Scenarios for an Integrated Europe: Driving Forces of Change and Quantitative Forecasts - Roberta Capello; Barbara Chizzolini; Ugo Fratesi (European Regional Science Association (ERSA), 2006)
The paper presents the second step of an ambitious research project, which has the aim to provide territorial scenarios of the New Europe in 15 years, developed under different hypotheses on the most important driving forces of change in the fields of economy, demographic, society, technology and institutions. The first step was presented last year at the ERSA conference in Amsterdam. In that occasion, the paper dealt with the econometric model (labelled MASST – Macroeconomic, social, sectoral and territorial model) built for the forecasting activity, presenting its strengths and weaknesses and the main results obtained by the estimates of the model. In this paper the additional work is presented, and the main conceptual and methodological steps forward analysed. In particular, the aims of the paper are the following: - to present the main driving forces that influence the future of Europe and of its territory. These are of different nature: socio-cultural (future migration forces and future birth and death rates), institutional (deepening vs. widening of enlargement), macroeconomic (trend in the euro/ exchange rate, trend in fiscal morality – i.e. trend in public debts, revision of the Maastricht parameters -, trend in interest rates, trend in inflation rate, geo-political orientation of FDI, rebalancing of external accounts of big emerging countries; increase in energy price), political (reforms of the structural funds and of the Community Agricultural Policy); - to present the different hypotheses under which the scenarios are built. The idea is to build three scenarios, a baseline scenario, a competitive and a cohesive scenario, and to present the differences among them; - to present the results of the simulation. The MASST model is able to provide both regional GDP growth rates and GDP levels, as well as regional population growth rates, and population levels, for the three scenarios. The model is able to provide the simulations for 27 Countries (the old 15 EU members, the new 10 Countries and Bulgaria and Romania) and for their 259 regions.
Keywords: 330